2021
DOI: 10.1038/s41467-021-21822-z
|View full text |Cite
|
Sign up to set email alerts
|

Moiré excitons in MoSe2-WSe2 heterobilayers and heterotrilayers

Abstract: Layered two-dimensional materials exhibit rich transport and optical phenomena in twisted or lattice-incommensurate heterostructures with spatial variations of interlayer hybridization arising from moiré interference effects. Here, we report experimental and theoretical studies of excitons in twisted heterobilayers and heterotrilayers of transition metal dichalcogenides. Using MoSe2-WSe2 stacks as representative realizations of twisted van der Waals bilayer and trilayer heterostructures, we observe contrasting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 55 publications
7
66
1
1
Order By: Relevance
“…Due to the aforementioned complexities of the electronic band structure, the exact origin or these peaks is still a matter of debate. Depending on the experimental evidence and insight from theoretical calculations, the PL signals were attributed to 1) a mix of momentum direct (KK) and momentum‐indirect (KQ) interlayer excitons, evidenced by the different temperature behaviors of the PL peak lifetimes; [ 36,43 ] 2) to a pair of momentum‐indirect KQ excitons, with an energy separation due to the spin–orbit splitting of the conduction band valley at the Q point, evidenced by the observed opposite circular polarization; [ 47 ] 3) a singlet–triplet pair of neutral, momentum‐direct, excitons at the K and K ′ points, evidenced by recent measurements of the interlayer exciton PL under application of external magnetic fields; [ 48–51 ] and 4) a pair of spatially indirect neutral exciton and spatially indirect negatively charged trion, evidenced by an observed constant relative intensity of the two PL signals at low temperature, [ 40 ] but somewhat contradicted by the circular polarization response reported by other authors. For structurally similar MoS2/WS2 heterobilayers, experimental reports suggest the existence of three interlayer exciton peaks, which were attributed to KK, QΓ, and KΓ transitions based on a combination of optical measurements and theoretical simulations using the excitonic Bethe–Salpeter Equation (BSE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the aforementioned complexities of the electronic band structure, the exact origin or these peaks is still a matter of debate. Depending on the experimental evidence and insight from theoretical calculations, the PL signals were attributed to 1) a mix of momentum direct (KK) and momentum‐indirect (KQ) interlayer excitons, evidenced by the different temperature behaviors of the PL peak lifetimes; [ 36,43 ] 2) to a pair of momentum‐indirect KQ excitons, with an energy separation due to the spin–orbit splitting of the conduction band valley at the Q point, evidenced by the observed opposite circular polarization; [ 47 ] 3) a singlet–triplet pair of neutral, momentum‐direct, excitons at the K and K ′ points, evidenced by recent measurements of the interlayer exciton PL under application of external magnetic fields; [ 48–51 ] and 4) a pair of spatially indirect neutral exciton and spatially indirect negatively charged trion, evidenced by an observed constant relative intensity of the two PL signals at low temperature, [ 40 ] but somewhat contradicted by the circular polarization response reported by other authors. For structurally similar MoS2/WS2 heterobilayers, experimental reports suggest the existence of three interlayer exciton peaks, which were attributed to KK, QΓ, and KΓ transitions based on a combination of optical measurements and theoretical simulations using the excitonic Bethe–Salpeter Equation (BSE).…”
Section: Introductionmentioning
confidence: 99%
“…[ 54 ] Based on magnetoluminescence experiments, a recent study suggested that the interlayer PL peaks in twisted MoSe2/WSe2 heterobi‐ and trilayer systems in R registry arise from moiré potential modulated momentum‐direct and phonon‐assisted momentum‐indirect interlayer exciton emissions. [ 51 ]…”
Section: Introductionmentioning
confidence: 99%
“…To complement our theory analysis of excitons in 2H and 3R WSe 2 BLs, we determined the exciton g-factors from magneto-luminescence measurements and correlated them with theoretically calculated values in different spin, valley and layer configurations [28,65]…”
Section: Initial Characterization Of the Two Distinct Crystal Configurations Was Performed Withmentioning
confidence: 99%
“…Q) interlayer excitons, evidenced by the different temperature behaviors of the PL peak lifetimes; [36,43] 2) to a pair of momentum-indirect K ! Q excitons, with an energy separation due to the spin-orbit splitting of the conduction band valley at the Q point, evidenced by the observed opposite circular polarization; [47] 3) a singlet-triplet pair of neutral, momentum-direct, excitons at the K and K 0 points, evidenced by recent measurements of the interlayer exciton PL under application of external magnetic fields; [48][49][50][51] and 4) a pair of spatially indirect neutral exciton and spatially indirect negatively charged trion, evidenced by an observed constant relative intensity of the two PL signals at low temperature, [40] but somewhat contradicted by the circular polarization response reported by other authors. For structurally similar MoS 2 /WS 2 heterobilayers, experimental reports suggest the existence of three interlayer exciton peaks, which were attributed to K !…”
Section: Introductionmentioning
confidence: 99%
“…[54] Based on magnetoluminescence experiments, a recent study suggested that the interlayer PL peaks in twisted MoSe 2 /WSe 2 heterobi-and trilayer systems in R registry arise from moiré potential modulated momentum-direct and phonon-assisted momentum-indirect interlayer exciton emissions. [51] On the theoretical side, accurate ab initio investigations of the excitonic spectra of van-der-Waals heterostructures are limited to rather small and symmetric systems due to the delicate interplay of quasiparticle band structure, effects from interlayer interaction and spin-orbit coupling and (computationally expensive) Coulomb interaction between electrons and holes. Despite these constraints, a number of studies using various methods have been reported recently, typically focusing on the properties of momentum-direct interlayer excitons [52,[54][55][56][57][58][59] and trions.…”
Section: Introductionmentioning
confidence: 99%